The Competitive Advantage of Online Market New Normal COVID-19 - Mathuros, Suwimon; Kuljittree, Sirintip; Rattanarasri, Kitti (Rajapark Journal, 2022)
The academic article on the competitive advantage of the online market new normal COVID-19 had the objective of presenting the concept of appropriate online marketing competition management during the COVID-19 period. Therefore, we would like to propose as follows: 1) decision making; 2) concept of consumer behavior; and 3) concepts of Thai e-commerce in the post- COVID-19 by studying the competitive advantages of online marketing in the new normal COVID-19. Entrepreneurs who have to adjust to changing online marketing competition, which is in line with the new normal (New Normal). With management guidelines for trade advantages such as product quality, fast delivery, and marketing and advertising costs. From the situation of the epidemic of COVID-19 that affects the sale of goods, the change in sales methods after sales service restrictions on access to customer groups bring technology to support, including the behavior of consumers who want convenience in ordering products.